Finite Element Modeling of Mode I Failure of the Single Contoured Cantilever CFRP-Reinforced Concrete Beam. (24th December 2013) - Nicholas, T.; Boyajian, D.; Chen, S. E.; Zhou, A.
Abstract : The single contour cantilever beam (SCCB) test method has been developed with the intent to capture Mode I opening failures of CFRP-reinforced concrete beams. Recent development in the method explores possible shifting damage into the concrete substrate by using the International Concrete Repair Institute (ICRI) Surface Profile Level Three (SP3) as the desired CFRP bonded interface to concrete. To validate and explain the interface fracture behavior, finite element analysis using special cohesive elements has been performed. The cohesive element allows separation of the concrete substrate from the CFRP. This paper presents the simulation of laboratory test results, where failure in the substrates has been successfully reproduced. The simulation results indicate that finite element method using cohesive elements can successfully replicate Mode I critical strain energy release rate and the peak capacity of the laboratory tests and may have the potential to simulate actual applications.